ChemInform Abstract: Copper‐Catalyzed Selective Single Arylsulfanylation of Aryl Diiodides with Aryl Thiols. Issue 14 (8th April 2014) - Liu, Yunyun; Wang, Hang; Cao, Xiaoji; Fang, Zheng; Wan, Jie‐Ping
Abstract The title reaction gives rise to the formation of a broad array of iodine‐functionalized diarylsulfides (III) (22 examples).